2016
DOI: 10.1002/ejoc.201501329
|View full text |Cite
|
Sign up to set email alerts
|

Mono‐ and Difluorination of Benz­ylic Carbon Atoms

Abstract: This microreview is divided into four parts: introduction, benzylic monofluorination, benzylic difluorination and summary. Each procedure (base-mediated, transition-metal-catalyzed, radical-initiated benzylic fluorination) is described for the cases of both electrophilic and nucleophilic fluorine sour-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 62 publications
(44 reference statements)
0
24
0
2
Order By: Relevance
“…In this context, the advantage of direct C-H fluorination over traditional fluorination methods is that it does not require the introduction of other functional groups. Although many methods have been developed for fluorination reactions [3,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46], including the addition of electrophilic fluorine to alkenes [1,28,32], the fluorination of aryl triflates [29] and arylpalladium complexes [2,47], few permit a one-step transformation of unactivated C(sp 3 )-H bonds to C(sp 3 )-F bonds [1,3,36,38,48]. Such a transformation would be highly valuable for the late-stage functionalization (LSF) of complex molecules, such as those in Scheme 1.…”
Section: Relevance Of Direct C-h Fluorination Methodsmentioning
confidence: 99%
“…In this context, the advantage of direct C-H fluorination over traditional fluorination methods is that it does not require the introduction of other functional groups. Although many methods have been developed for fluorination reactions [3,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46], including the addition of electrophilic fluorine to alkenes [1,28,32], the fluorination of aryl triflates [29] and arylpalladium complexes [2,47], few permit a one-step transformation of unactivated C(sp 3 )-H bonds to C(sp 3 )-F bonds [1,3,36,38,48]. Such a transformation would be highly valuable for the late-stage functionalization (LSF) of complex molecules, such as those in Scheme 1.…”
Section: Relevance Of Direct C-h Fluorination Methodsmentioning
confidence: 99%
“…This inconvenience has been overcome by introducing a fluorine atom onto the piperidine ring (130, Figure 18), reducing the basicity of the secondary amine by nearly two orders of magnitude, resulting in a marked betterment The beneficial properties of benzyl fluorides in lead optimization 102,103 have motivated an intense research activity in late stage fluorination of benzylic positions. 101 Britton and colleagues 104 have reported a late-stage fluorination of benzylic positions employing NFSI using either a decatungstate photocatalyst or AIBN-initiation.…”
Section: -Methods For Fluorination Of Sugars and Nucleobase Derivatmentioning
confidence: 99%
“…However, only in recent years has benzylic fluorination started to gain increased attention, proving to be a powerful tool for site-specific C(sp 3 )-F bond formation. 93,[104][105][106][107][108][109][110][111][112][113][114] Generally, amongst these studies, different fluorination routes can be identified: (i) electrophilic fluorination employing Selectfluor®, N-fluoropiridinium salts and NFSI as fluorinating sources, 93,[104][105][106][107] (ii) nucleophilic fluorination with triethylamine trihydrofluoride, TREAT•HF, and fluor-ide salts, 108,109 and (iii) thermal-or photocatalysed radical fluorination. [110][111][112][113] Amongst these, benzylic fluorination catalysed by transition metal complexes using electrophilic fluorinating reagents represents the most exploited (see examples in Scheme 10, entries 1-3).…”
Section: Benzylic Fluorinationmentioning
confidence: 99%